Characterization of Aromatic Liquor by Gas Chromatography and Principal Component Analysis. (24th March 2017) - Han, Sihai; Zhang, Weiwei; Li, Peiyan; Li, Xuan; Liu, Jianxue; Xu, Baocheng; Luo, Denglin
ABSTRACT: The differentiation of aromas of Chinese liquor is important for their unique flavors. In this work, aromas of Chinese liquor were characterized by gas chromatography and chemometrics. Ten representative aroma compounds, including three alcohols, four esters, two organic acids, and acetal in 16 Chinese liquor were determined by gas chromatography with flame ionization detection. The relationship between these compounds and six classic aromas was investigated using principal component analysis and k -means clustering. The cumulative contribution of the first three principal components reached up to 84.607%, which effectively differentiated the liquors. The variables with the highest loading absolute value were acetal and ethyl acetate for principal component 1, ethyl butanoate and ethyl hexanoate for principal component 2, and the hexanoic acid and ethyl butanoate for principal component 3. The aromas of the liquors were characterized by k -means clustering with the first three principal component scores, indicating that the acetal, ethyl acetate, ethyl butanoate, ethyl hexanoate, and hexanoic acid are important for the aroma of Chinese liquors. This work demonstrated that the gas chromatography with chemometrics is effective for the characterization of aromatic liquor.